Effectiveness of the Plastic-Free Campus Movement in Promoting Sustainable Lifestyles and Supporting SDG 12.5 among Biology Students - Nikita Ar Rani; Herlina Fitrihidajati; Adi Candra; Nurcholis (Indonesian Journal of Mathematics and Natural Science Education, 2026)
Single-use plastic waste remains a major environmental challenge on university campuses due to its intensive use and low degradability, increasing waste management burdens and pollution risks. This study evaluated the effectiveness of the Plastic-Free Campus Movement in promoting sustainable lifestyles among Biology students and reducing single-use plastic waste on campus. A one-group pre-test–posttest pre-experimental design with quantitative descriptive and observational approaches was employed involving 80 Biology and Biology Education students at the Faculty of Mathematics and Natural Sciences, State University of Surabaya. Data were collected through pre-tests, post-tests, attitude and response questionnaires, and waste-volume observation sheets, and analysed using descriptive statistics, the Shapiro–Wilk normality test, the Wilcoxon signed-rank test, and N-gain analysis. The educational media and research instruments were highly valid with a feasibility score of 100%. Students' knowledge increased significantly from 54.55 to 92.76 (p < 0.05) with a high N-gain score (0.84). Student attitudes (84.55%) and programme responses (82.47%) were categorised as very good. In addition, the average plastic waste-bin occupancy decreased from an overflow condition equivalent to 104% of bin capacity in the first week to 24% of bin capacity by the fourth week. These findings demonstrate that the Plastic-Free Campus Movement effectively improved students' environmental awareness and sustainable behaviour while contributing to measurable reductions in campus plastic waste, providing a practical educational strategy to strengthen Green Campus initiatives and support SDG 12.5.